Collaboration, decarbonization, and distributional effects. (1st July 2023) - Mier, Mathias; Siala, Kais; Govorukha, Kristina; Mayer, Philip
Abstract: We use a CIB analysis and a CGE model to develop decarbonization scenarios for the European power market. Our CIB analysis reveals qualitative scenarios that differ in the level of political (stringency of climate policy) and physical collaboration (transmission grid expansion). The CGE model quantifies those scenarios for further usage in the power market model EUREGEN to analyze related distributional effects across heterogeneous countries as well as between consumers and producers. EUREGEN predicts that consumers experience considerably higher electricity prices in the future in all scenarios, whereas producers observe higher rents. Electricity prices are lowest in the least collaborative future. Producer rents in turn are highest in the most collaborative one. Patterns hugely differ by country, making 13 countries to profiteers of the least collaborative future and 12 countries to profiteers of the most collaborative one. Only 3 countries profit from medium collaboration. Countries that profit from the most collaborative future experience substantially higher producer rents. Countries that profit from the least collaborative one in turn experience lowest electricity prices.